Validation of Non-invasive Language Mapping Modalities for Eloquent Tumor Resection: A Pilot Study - Muir, Matthew; Patel, Rajan; Traylor, Jeffrey; de Almeida Bastos, Dhiego Chaves; Prinsloo, Sarah; Liu, Ho-Ling; Noll, Kyle; Wefel, Jeffrey; Tummala, Sudhakar; Kumar, Vinodh; Prabhu, Sujit (Frontiers in Neuroscience, 2022)
Many studies have established a link between extent of resection and survival in patients with gliomas. Surgeons must optimize the onco-functional balance by maximizing the extent of resection and minimizing postoperative neurological morbidity. Preoperative functional imaging modalities are important tools for optimizing the onco-functional balance. Transcranial magnetic stimulation (TMS) and functional magnetic resonance imaging (fMRI) are noninvasive imaging modalities that can be used for preoperative functional language mapping. Scarce data exists evaluating the accuracy of these preoperative modalities for language mapping compared to gold standard intraoperative data in the same cohort. This study compares the accuracy of fMRI and TMS for language mapping compared to intraoperative direct cortical stimulation (DCS). We also identify significant predictors of preoperative functional imaging accuracy as well as significant predictors of functional outcomes. Evidence from this study could inform clinical judgement as well as provide neuroscientific insight. We used geometric distances to determine co-positivity between preoperative data and intraoperative data. Twenty eight patients were included who underwent both preoperative fMRI and TMS procedures as well as an awake craniotomy and intraoperative language mapping. We found that TMS shows significantly superior correlation to intraoperative DCS compared to fMRI. TMS also showed significantly higher sensitivity and negative predictive value than specificity and positive predictive value. Poor cognitive baseline was associated with decreased TMS accuracy as well as increased risk for worsened aphasia postoperatively. TMS has emerged as a promising preoperative language mapping tool. Future work should be done to identify the proper role of each imaging modality in a comprehensive, multi-modal approach to optimizing the onco-functional balance.